Activated Protein C Does Not Alleviate the Course of Systemic Inflammation in the APCAP Trial - Lea Kyhälä; Panu Mentula; Leena Kylänpää; Eeva Moilanen; Pauli Puolakkainen; Ville Pettilä; Heikki Repo (International Journal of Inflammation)
The study aimed to determine the effect of the activated protein C on the course of systemic inflammation in the APCAP (activated protein C in acute pancreatitis) trial where we randomized 32 patients with severe acute pancreatitis to receive either recombinant activated protein C (drotrecogin alfa activated) (n=16) or placebo (n=16) for 96 hours. In the present study, we present the time course of the patients’ plasma or serum levels of soluble markers (IL-8, IL-6, IL-10, IL-1ra, sE-selectin, PCT) and monocyte and neutrophil cell surface (CD11b, CD14, CD62L, HLA-DR) markers of systemic inflammatory response during the first 14 days after the randomization. The results of the intervention and placebo groups were comparable showing that recombinant APC treatment did not alter the course of systemic inflammation in severe acute pancreatitis. Our finding is in accordance with the clinical findings in the APCAP trial indicating that the intervention did not affect evolution of multiple organ dysfunctions.